Studi komparasi kompetensi siswa sebelum dan sesudah penggunaan bahan ajar ipa terpadu bermuatan literasi saintifik tema kesehatan pencernaan kelas VIII SMPN 8 Padang - putri afrasti; yurnetti yurnetti; Asrizal Asrizal (Universitas Negeri Padang, 2019)
Science teaching in junior high school based on the 2013 curriculum should be done in an integrated form. In this case, the integration of science material includes Physics, Chemistry, Biology and its applications. The real condition indicated that the integrated Science teaching in schools can’t be applied in accordance with expected condition. The solution of the problem is to apply the integrated science learning material by integrating the literacy. The purpose of the research was to determine the effect of the application of integrated Science learning material by integrating literacy on the digestive health theme in the scientific approach to the competency of grade VIII students in SMPN 8 Padang. This type of research was quasi-experimental research with a before-after design. The research population was all grade VIII students of SMPN 8 Padang in the academic year 2018/2019. The research sample was obtained by both purposive sampling technique and cluster random sampling. The instrument of knowledge aspect of competency was written test in the form of multiple choice, skills aspect was performance assessment sheet, and attitudes aspect was observation sheet. The data analysis techniques in the research were descriptive statistical analysis, normality test, homogeneity test, paired comparison test and Wilcoxon test. From the data analysis, it can be concluded that the application of integrated Science learning material by integrating literacy has a significant effect on the three competencies of grade VIII students including knowledge, skills, and attitudes at the 95% confidence level.